Exploring coordinated development between urbanization and ecosystem services value of sustainable demonstration area in China- take Guizhou Province as an example. (November 2022) - Zhao, Yangling; Shi, Yu; Feng, Chen-Chieh; Guo, Luo
Graphical abstract: Highlights: The heterogeneous ecosystem service units were identified. The space–time patterns of urbanization level were evaluated. The level of coupling and coordination between urbanization and ecosystem services is getting higher and higher during the study period. The types of coupling and coordination between urbanization and ESV are different in different cities, mainly with lagging urbanization, followed by synchronous development. Abstract: As one of the first ecological civilization demonstration areas in China, Guizhou Province, an underdeveloped region, experienced rapid economic development. The resulting human activities at an accelerated rate in Guizhou Province put great pressure on its environmental carrying capacity, especially the Karst landscape in the region. Understanding the relationship between urbanization and ecosystem services in Guizhou Province is indispensable for the sustainable development of the region in the future. Based on remote sensing data from 1990 to 2020, this study explores the spatiotemporal dynamics of ecosystem services value (ESV) and urbanization, as well as the degree of coupling and coordination (CCD) between them. The result suggested that between 1990 and 2020, the ESV of Guizhou Province showed a two-step decline due to the conversion of forest land for agricultural and urban usage. In addition, the ESV of the western region is lower than its eastern counterpart. The CCD level between ESV and urbanization has increased over time, but most areas are still in an unbalanced state of development. Most areas are mainly urbanization lagging, but the central and north-central research areas are mainly ESV lagging. Identifying the regional differences of coupling coordination types has shed light on the degree of contradiction between local urbanization and ESV, and helped find the balance between ecological sustainability and urbanization.